2007
DOI: 10.1088/1478-3975/4/4/008
|View full text |Cite
|
Sign up to set email alerts
|

Curvature-driven lateral segregation of membrane constituents in Golgi cisternae

Abstract: Lateral segregation of mobile membrane constituents (e.g. lipids, proteins or membrane domains) into the regions of their preferred curvature relaxes stresses in the membrane. The equilibrium distribution of the constituents in the membrane is thus a balance between the gains in the membrane elastic energy and the segregation-induced loss of entropy. The membrane in the Golgi cisternae is particularly susceptible to the curvature-driven segregation because it possesses two very different curvatures-the highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
46
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 24 publications
4
46
2
Order By: Relevance
“…8). Indeed, in agreement with previous experimental and theoretical studies [19][20][21][22][23][24] , lipid sorting by membrane shape is not efficient when physiological radii are considered and does not correct significantly lipidpacking defects.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…8). Indeed, in agreement with previous experimental and theoretical studies [19][20][21][22][23][24] , lipid sorting by membrane shape is not efficient when physiological radii are considered and does not correct significantly lipidpacking defects.…”
Section: Discussionsupporting
confidence: 91%
“…Most lipids are flexible molecules and, through shape adjustment, might minimize unfavourable exposure of their hydrocarbon chains to water. In addition, lipids with noncylindrical shape (for example, lysolipids or diacylglycerols) could distribute non-randomly within regions of different curvature to reduce geometrical mismatches, although the efficiency of such a mechanism has been questioned due to the propensity of lipids to readily mix through the entropic effect [19][20][21][22][23][24] .…”
mentioning
confidence: 99%
“…From Table 2, the curvature preference of all the NBD-labeled lipids would become very low (<10%) in SUVs with a diameter larger than 100 nm. These observations support predictions of coarse-grained molecular-dynamic simulations in SUVs (20,21) and theoretical studies (2,19).…”
Section: Discussionsupporting
confidence: 85%
“…Not all lipids form the H II phase; however, the spontaneous curvature of some other lipids can be estimated by analyzing the perturbation in the periodicity of the DOPE H II phase caused by the addition of the second lipid type (17,18). Theoretical studies based on these measurements (2,19) and molecular-dynamic simulations (20,21) suggested that the curvature preference of lipids is weaker than that observed in biological systems. Consistent with these studies, no significant sorting of lipids into membrane nanotubes was observed (22,23).…”
mentioning
confidence: 99%
“…Both C 0 and k depend on the composition of the curved patch. If this patch is more curved than its surroundings, the bending energy can be lowered by adjusting the composition to reduce k and/or to have C 0 match C. This idea has been explored theoretically, with special emphasis on the interplay between lipid inhomogeneity and the mechanical properties of vesicles (Markin 1981;Seifert 1993;Derganc 2007;Jiang and Powers 2008;Sorre et al 2009). …”
mentioning
confidence: 99%